2019
DOI: 10.3390/ijerph16234661
|View full text |Cite
|
Sign up to set email alerts
|

E-Liquid Flavor Preferences and Individual Factors Related to Vaping: A Survey among Dutch Never-Users, Smokers, Dual Users, and Exclusive Vapers

Abstract: Appealing product characteristics, such as flavors, may stimulate e-cigarette use. While switching to e-cigarettes may reduce harm for smokers, concerns exist about e-cigarette use among never-smokers. The role of flavors in the decision to switch to or refrain from vaping is unclear. This study used a bottom–up approach to investigate the relation between flavor preferences and individual factors related to vaping between various user groups. A cross-sectional survey was conducted among never-users (n = 407),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
(98 reference statements)
0
24
0
Order By: Relevance
“…Researchers found that youth who had used an e-cigarette were 3.5 times more likely to use marijuana compared to youth who had not used an e-cigarette [ 19 ]. In a Dutch cross-sectional survey, it was found that access to a variety of flavors is one of the most attractive characteristics prompting initial vape use [ 12 ]. In our study, flavor was not found to be a significant factor influencing vape use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers found that youth who had used an e-cigarette were 3.5 times more likely to use marijuana compared to youth who had not used an e-cigarette [ 19 ]. In a Dutch cross-sectional survey, it was found that access to a variety of flavors is one of the most attractive characteristics prompting initial vape use [ 12 ]. In our study, flavor was not found to be a significant factor influencing vape use.…”
Section: Discussionmentioning
confidence: 99%
“…Vape products come in a variety of styles, and there are over 7,000 available flavors in the market [ 9 - 11 ]. A cross-sectional survey in a large cohort (N = 728) was carried out to examine the relationship between product characteristics and e-cigarette appeal [ 12 ]. Of participants that exclusively vaped, 68.9% reported that the option of different flavors was the most attractive characteristic of using vapes that influenced their decision to begin vaping [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that vape tricks may attract adults too. In a small survey (n=183 ENDS users) conducted in the Netherlands 24.6% endorsed cloud chasing tricks as an attractive feature of ENDS [77]. Attractive features, such as the generation of very dense aerosols, appear to entice people into using these products and not just flavors.…”
Section: Misrepresentation On the Role Of Flavoursmentioning
confidence: 99%
“…18,29 Surveys have shown that the availability of different flavors is among the most attractive features of e-cigarettes in this age group. 30 Teenage vaping, in turn, has been shown to increase the likelihood of smoking, with or without concurrent e-cigarette use, later in life. 31,32,33 A review study found that adolescents, males, and white people are more likely than other groups to consume e-cigarettes in the United States and several other countries.…”
mentioning
confidence: 99%